Alveolar fibroblast lineage orchestrates lung inflammation and fibrosis - Tsukui, Tatsuya; Wolters, Paul J.; Sheppard, Dean (Nature (London), 2024)
Fibroblasts are present throughout the body and function to maintain tissue homeostasis. Recent studies have identified diverse fibroblast subsets in healthy and injured tissues 1 , 2 , but the origins and functional roles of injury-induced fibroblast lineages remain unclear. Here we show that lung-specialized alveolar fibroblasts take on multiple molecular states with distinct roles in facilitating responses to fibrotic lung injury. We generate a genetic tool that uniquely targets alveolar fibroblasts to demonstrate their role in providing niches for alveolar stem cells in homeostasis and show that loss of this niche leads to exaggerated responses to acute lung injury. Lineage tracing identifies alveolar fibroblasts as the dominant origin for multiple emergent fibroblast subsets sequentially driven by inflammatory and pro-fibrotic signals after injury. We identify similar, but not completely identical, fibroblast lineages in human pulmonary fibrosis. TGFβ negatively regulates an inflammatory fibroblast subset that emerges early after injury and stimulates the differentiation into fibrotic fibroblasts to elicit intra-alveolar fibrosis. Blocking the induction of fibrotic fibroblasts in the alveolar fibroblast lineage abrogates fibrosis but exacerbates lung inflammation. These results demonstrate the multifaceted roles of the alveolar fibroblast lineage in maintaining normal alveolar homeostasis and orchestrating sequential responses to lung injury. In mouse and human, lung-specialized alveolar fibroblasts adopt multiple molecular states that are induced by pro-inflammatory and fibrotic signals and have diverse protective roles against lung injury.